Self-adjointness and conservation laws for Kadomtsev–Petviashvili–Burgers equation. (June 2015) - Wei, Long; Zhang, Jiezi
Abstract: In this work we study the Kadomtsev–Petviashvili–Burgers equation, which is a natural model for the propagation of the two-dimensional damped waves. We show that the equation is nonlinear self-adjoint and it will become strict self-adjoint or weak self-adjoint in some equivalent form. By using Ibragimov's theorem on conservation laws we find some conservation laws for this equation.